Autopolyploidy-driven range expansion of a temperate-originated plant to pan-tropic under global change - Cheng, Jiliang; Li, Jun; Zhang, Zheng; Lu, Huan; Chen, Guoqi; Yao, Beibei; Dong, Yingxue; Ma, Ling; Yuan, Xiaoxiao; Xu, Jingxuan; Zhang, Ying; Dai, Weimin; et al. (Dryad, 2020)
Angiosperms are believed to have emerged initially in the tropics and
expanded their distribution range polewards through diverse mechanisms,
for example polyploidization-driven cold-tolerance evolution. Reversed
expansion from temperate to pantropic climate through a
polyploidization-driven shift in heat-tolerance remains largely unknown.
Here, we found autopolyploidy in relation to the global expansion of
Solidago canadensis from its temperate-climate native range in North
American to hot-summer climate in an introduced range. Our
cytogeographical study of 2062 accessions from 471 locations worldwide
demonstrates that ploidy levels correlates negatively with latitude and
positively with average temperature. An isotherm-dependent shift of the
climate niches at the threshold of 20-24ºC between geo-cytotypes can be
attributed mainly to autopolyploidy-driven differentiation of heat
tolerance; only polyploids and not diploids are able to complete sexual
reproduction, germinate and grow in the hot-summer climate of low
latitudes. Ploidy-dependent fertility appears to play a key role in the
hot-summer introduced range in the northern hemisphere through both
pre-adaptation and rapid post-introduction adaptive evolution of delayed
flowering and improved heat-tolerance during embryo development. MaxEnt
model predicts continuous expansion of this weed under global change.
These results provide new insights into the mechanisms governing
autopolyploidy-driven backward range-expansion of plant species from
temperate origins.
Field sampling We collected seeds and leaf samples from up to 21 (median =
5) individuals from 78 locations in the native (NA) ranges (64 from the
US, 14 from Canada) and 72 locations in the introduced (IN) ranges (4 from
Japan, 1 from Russia, 3 from Europe, 1 from India, 63 from China), as well
as two fields in China (Lianyungang, Jiangsu and Kunming, Yunnan), where
the species was cultivated for sale as cut flowers (Supporting Information
Table S1-3). At each site, sampling plots were separated by 10 m to
minimize the chance of sampling multiple ramets from individual genets.
For populations from India and 40 Chinese populations, leaf samples were
collected from plants which were generated from field-collected rhizomes
grown in a common garden. Leaf samples were silica-dried to allow DNA
extraction for molecular identification of the species (ITS and psbA-trnH
sequencing), and seed samples were air dried at room temperature prior to
experiments. Molecular identification To confirm the correct
identification of each of the 152 collected populations, we sequenced the
ribosomal ITS (608bp) and psbA-trnH (213bp) intergenic spacer of up to
five individuals from each population (Table S1, S2). To this end, we
extracted total DNA from the dried leaves using a Plant Genomic DNA kit
(DP305, TIANGEN BIOTECH CO., LTD, Beijing, China). The detailed
information on primers and PCR reaction system and cycle conditions is
presented in the Supplementary Information. The ribosomal ITS and
chloroplast psbA-trnH were sequenced and edited using the DNAstar EdiSeq
software. As the reference for alignment, we extracted the data for S.
canadensis (ITS, HQ142590.1; psbA-trnH, KX214929.1) from GenBank and
aligned them with the ITS and psbA-trnH sequences of our samples using the
Clustal X 1.83 software. The ITS1, 5.8S and ITS2 gene boundaries and
psbA-trnH were determined from ITS and psbA-trnH sequences of the Solidago
genus in GenBank. To further verify the species identity of our samples,
we conducted a BLAST search in the database of the National Center for
Biotechnology Information (NCBI) to determine the species with the most
similar identities (Table S1, S2). In addition, we built phylogenetic
trees (Fig. S1, S2) for our samples with the ITS and psbA-trnH sequences,
using the MEGA 4.1 Beta 3 software based on the principle of maximum
parsimony method. We assessed branch support with 2,000 bootstrap
replicates. Determination of ploidy level First, as a (diploid) reference
for the ploidy-level determination, we assessed the exact chromosome
numbers of the progeny from each of the 13 accessions/seed families of the
Canadian population CA09 (Table S3, Fig. S3a), using mitotic root-tip
squashes under a microscope. We grew up plants from each seed
family/accession in the greenhouse, except for the Chinese and Indian
populations for which field samples of maternal plants were used for
ploidy examination. Fresh leaf material was held in self-sealing plastic
bags containing silica and transported to the laboratory for ploidy level
determination. We applied a modified flow cytometry method by Galbraith et
al. (1983) for the determination of ploidy level. Briefly, 0.5 g fresh
leaf tissue was chopped up with a razor blade in 2 ml of ice-cold
Galbraith buffer (PH7.0, 45mM MgCl2, 30mM sodium citrate, 20mM
4-morpholinepropane sulfonate, 0.5% w/v polyvinylpyrrolidone and Triton
X-100 1 mg/ml) in a vitreous Petri dish held on a chilled brick. The
resultant fine slurry was filtered through a 50μm microfilter into 2 ml
polystyrene tubes and incubated at 4 oC for 5min. The final filtrate was
treated with 10 μL/ml of RNase A for 10 min at 4°C. Then, 200 μL/ml of a
propidium iodide (PI) staining solution was added and incubated at 4°C for
30 min in darkness. The fluorescence strength of PI-DNA conjugates was
measured by flow cytometric (BD FACS, USA) using a 488 nm laser and 590/40
emission filter (Arumuganathan & Earle 1991). The diploid CA09
population (Table S3) was used as an external reference. Flow-cytometry
data acquisition and analysis was done with the software FloMax version
2.0 (Quantum Analysis, Münster, Germany). Only histograms with CVs smaller
than 10% and with a minimum peak height of 50 particles were accepted.
Other histograms were discarded and corresponding samples were designated
no signal (Suda and Travnicek 2006). To ensure the measurement quality,
the external reference material (CA09, the fluorescence intensity scale at
position 50, Fig. S3a) were measured and analyzed at regular intervals in
the analysis process to verify the corresponding position of the peak of
new samples that indicates their ploidy levels. Accordingly, each sample
was identified as diploid (2x), tetraploid (4x) or hexaploid (6x). Based
on the combination of cytotype (2x/4x/6x) and geographical range (native
[NA] / introduced [IN]), we assigned each accession to one of the
following six geo-cytotypes: NA2x, NA4x, NA6x, IN2x, IN4x or IN6x. As some
of the 152 populations included more than one cytotype, the total number
of population × cytotype combinations was 233. We also extracted data on
chromosome numbers of 321 S. canadensis populations with known locations
from ISI-indexed journals, books and databases of cytological indices
(Index of Plant Chromosome Numbers [IPCN], International Organization of
Plant Biosystematics [IOPB] Chromosome Number Reports). Detailed
information about the published ploidy records are listed in Table S4. In
total, our study includes information on the 1172 newly collected
accessions/seed families for which we determined ploidy (Table S3) and 890
previously published ploidy records in 471 locations worldwide (Table S4).
We used these data points to create a cytogeographical map in ArcGIS 10.0
(Environmental Systems Research Institute, Redlands, California, USA). For
each of the 471 locations, we extracted the mean July temperature of each
sample site using ArcGIS 10.0. Using the temperature of the hottest month
(July) in the northern hemisphere, we try to guide the hypothesis that the
thermotolerance evolution of S. canadensis may occur in populations with
different ploidy levels. A Tukey test was used to detect differences among
the different geo-cytotypes separated by the latitude distribution and
mean July temperature of sample site. To examine whether the latitude
distribution and mean July temperature were affected by geocytotypes, we
used two-way ANOVA, with explanatory variables being origin (native,
introduced), ploidy level (diploid, tetraploid, hexaploid) and their
interaction. Seed germination at different temperatures Since not all 150
populations had enough seed, which were collected in field, only 30 native
and 56 introduced cytotype populations representing all geo-cytotypes were
tested in this experiment (Table S3 E1). We bulked the seeds from up to
five accessions (if available) from each population, and tested their
germination under two temperature regimes with a temperature of 25°C
(12h/12h, day/night) and an extreme temperature of 39°C (12h/12h,
day/night), respectively (the two temperatures were based on Li, 2011). A
total of 150 seeds from each population were divided into three sets as
three replicates. The 50 seeds were placed on wet filter paper in
petri-dish (diameter = 9 cm) and kept in the growth chamber (2 m long ×
0.8 m wide × 0.8 m high; Ningbo Jiangnan Biological Instrument factory,
Zhejiang, China). The photon flux density was 250 μmol m−2 s−1, with an
85% relative humidity (RH) in the chamber. The germination process was
observed every day lasted for 15 days, during which the filters were kept
wet. Petri-dishes were randomly distributed in chambers and their position
was changed every day. Seeds infected by fungi or bacteria were removed
and not considered for calculations, but the same number of new seeds were
added. A seed was considered as germinated if the radicle grew longer than
seed length. The seed germination inhibition rate was calculated using the
following equation: Inhibition rate = [(a-b)/a] × 100%, with “a” and “b”
representing mean germination rate of population at 25°C and 39°C. One-way
ANOVA was used for data analysis with Duncan’s parametric tests being
applied to compare the differences of the germination inhibition rate
among geo-cytotypes. Common garden comparative experiments To examine
ecological adaptation and reproduction of the different geo-cytotypes, two
comparative common garden experiments were conducted in the introduced
range (IRCG) at Nanjing Agricultural University (32º02′N, 118º50′E;
Nanjing, Jiangsu, China) and in the native range (NRCG) at the University
of Georgia (33º56′N, 83º22′W; Athens, GA, USA), respectively. The IRCG
experiments started on December 3, 2011 and December 5, 2012, while NRCG
ones did not begin until December 10, 2012. At IRCG, the mean annual
rainfall was 1090.7 mm, annual mean temperature was 15.6°C, mean max and
min temperatures in January were 7.2°C and -0.7°C, and mean max and min
temperatures in July were 32.2°C and 24.9°C. A total of 507 accessions
propagated from the 30 native and 56 introduced populations were used in
IRCG (population details in Table S3 E1). At NRCG, mean annual rainfall
was 1250.0 mm, annual mean temperature was 15.9°C, mean max and min
temperatures in January were 13.9°C and 1.4°C, and mean max and min
temperature in July were 32.8°C and 20.8°C. A subset of plants from 26
populations, including all geo-cytotypes, was grown in NRCG (population
details in Table S3 E2). At both common gardens, seeds from up to 5
maternal plants of each population were germinated in seedling trays
filled with a 1:2 mixture of soil and sterilized compost in a greenhouse
(18-25oC) in December. To minimize maternal effects associated with the
quality of sampled seeds, at least 30-day-old seedlings with similar
heights, basal diameters and leaf numbers were selected from each maternal
plant per population and individually transplanted into 11-cm-wide,
8-cm-deep, 1 L plastic pots containing the same growing medium. Potted
plants were randomly placed in a glasshouse supplemented with artificial
light for 16 h during the day and watered as needed, usually every 2-4
days. Each accession was grown individually outdoors in a 5-L plastic pot
filled with the same growing medium in March (three month after planting,
the daily average temperature was above 10 oC). Trays and pots were
reassigned randomly to new positions weekly. Pot management in two common
gardens was the same. To determine heat and frost tolerance with different
geo-cytotypes (Table S3 E1), seedlings of S. canadensis accessions were
transplanted to 1-L plastic pots filled with a 1:2 mixture of soil and
sterilized compost 30 days (January 2, 2013) after sown in the greenhouse
at IRCG. Two months later (March 3, 2013), the plants were divided into
three sets for different experiments. The first set of 516 plants (six
offspring individuals of 1 to 6 accessions from each population) was used
to determine the heat tolerance (beginning on March 3, 2013). Plants were
kept with saturated soil moisture and subjected to 45±1°C for 10h in a
growth chamber (E-36HO, PERCIVAL, U.S.), and assessed leaf heat damage.
Seedlings were assessed according to a heat-damage index: 0) for healthy
and normal seedlings; 1) when the tip of leaves was slightly burned; 2)
1-2 leaves were wilted; 3) 3-4 leaves were wilted; 4) > 4 leaves
were wilted; and 5) all leaves wilted. Heat-tolerance index (HI) was
calculated as 1-Σ[(number of seedling corresponding grade) / ( maximum
grade total number of seedling)]. The second set of 774 plants (nine
offspring individuals of 1 to 3 accessions from each population) was used
to examine physiological responses to high temperature (beginning on March
5, 2013). The 3rd to 5th leaves from the shoot apex of plant were sampled
and immediately frozen in liquid nitrogen and stored at -80°C until use
after exposing to 45±1°C for 0, 2 and 4h, respectively (room temperature
was about 28°C). The reactive oxygen species (ROS) levels (i.e. H2O2
content), activities of antioxidant enzymes including Cu/Zn superoxide
dismutase activity (Cu/Zn-SOD), peroxidase activity (POD), catalase
activity (CAT), glutathione reductase activity (GR), contents of
non-enzymatic antioxidants (ASA), and osmoregulatory substances (i.e.
soluble proteins) were assayed using commercial reagent kits purchased
from Nanjing Jiancheng Bioengineering Institute (Nanjing, China). The
third set of 430 plants (five offspring individuals of 1 to 5 accessions
from each population) was used to estimate freezing tolerance (beginning
on March 9, 2013). We examined the relative PIABS (performance index on
absorption basis) using chlorophyll-fluorescence measurements (Pocket-PEA,
Hansatech Instruments LTD., King’s Lynn, Norfolk, PE32 1JL. UK) (Xie et
al. 2015). The initial PIABS was measured after 30 min dark adaptation at
room temperature. The upper, middle and lower parts of both sides of veins
in each leaf (the fifth mature leaf) were measured. The freezing PIABS was
measured at the same part of each leaf after the exposure of detached
leaves to -8°C for 30 minutes. The relative PIABS = freezing PIABS/initial
PIABS (Xie et al. 2015). The relative PIABS represents the freezing
tolerance of S. canandensis. One-way ANOVA was used to analyze the
differences of heat-damage index, freezing tolerance (relative PIABS),
inhibition rate of germination, ROS level, SOD, POD, CAT, GR, ASA, and
soluble proteins among different geo-cytotypes. Duncan’s test was applied
when assumptions of normality and homogeneity of variance were fulfilled;
otherwise non-parametric ANOVA (Dunnett’s C test) would be used. In
addition, to confirm the effect of environmental temperature factors on
plant heat tolerance, we used canonical correspondence analysis (CCA) to
assess the relationship between “species factors” and “environmental
factors” as implemented in CANOCO for Windows 4.5 (Ter Braak &
Smilauer 2002). For species factors, we included the heat-damage index,
ROS level (H2O2 content) and antioxidative parameters. For environmental
factors, we included latitude and six bioclimatic variables, including
annual mean temperature (bio 1), isothermality (bio 3), minimum
temperature of coldest month (bio 6), mean temperature of driest quarter
(bio 9), mean temperature of warmest quarter (bio 10) and mean temperature
of coldest quarter (bio 11). Furthermore, because “species factors” also
were significantly affected by “ploidy level”, we also included “ploidy
level” as an environmental factor. To examine reproductive biology, we
kept S. canadensis plants in both common gardens, with 860 pots of plants
involved in IRCG (March 30, 2012 and 2013; Table S3 E1) and 260 pots in
NRCG (April 4, 2013; Table S3 E2). In both common gardens, we assessed
flowering phenology (onset, peak and end of flowering) and the number of
viable seeds produced per plant. The latter was based on the number of
seeds per plant and the germination rate at 25°C for each population (the
details are described as above). One-way ANOVA was used to analyze the
data for first flowering dates, flowering duration and number of viable
seeds among the six geo-cytotypes. Duncan’s test or Dunnett’s C test was
applied to separate means following the principle described above. An
additional set of measurements was taken only in IRCG in 2012. Because
plants from some of native-range North American populations failed to
produce viable seeds, we tested for pollen viability (Table S3 E5), stigma
receptivity (Table S3 E6), germination rates of pollen grains on stigmas
(Table S3 E7) and pollen-tube growth (Table S3 E7) for these native
populations. As S. canadensis is self-incompatible and the different
cytotypes are not cross-compatible (Yao 2014), we always used pollen and
stigmas from different plants of the same cytotype in a population. We
also recorded the mean and maximum daily temperatures during embryo
development of plants from native populations to assess the relationship
between embryo development and high temperatures (Table S3 E3). To assess
the impact of high temperatures on seed sterility more accurately,
additional measurements were taken also in IRCG in 2014 by transferring
offspring of 48 maternal plants from 16 populations (Table S3 E4) that did
not produce viable seeds in IRCG to a climatic chamber (Room C3006 in
Collage of Life Science, Nanjing Agariculture University) with a
temperature regime of 24/18°C (12h/12h, day/night, the photon flux density
was 250 μmol m−2 s−1) before flowering in July 2014. These populations
included four NA2x, four NA4x, four NA6x and four IN2x populations. In
addition, offspring of 24 maternal plants from 4 populations each of IN4x
and IN6x that could produce viable seeds in IRCG were also transferred to
the climatic chamber with a temperature regime of 36/30°C (12h/12h,
day/night) before flowering in Oct. 2014 (Table S3 E4). An identical set
of plants that included the above 24 populations was also prepared and
placed outdoors in the common garden to serve as controls. The daily
management of all experimental plants was the same to ensure their normal
and comparable growth. Plants belonging to the same cytotype and grown
under the natural and controlled conditions were artificially pollinated
with the pollen from each other. Seeds per plant were harvested when
mature and the number and germination rate of well-developed seeds were
determined and used to estimate the number of viable seeds. Potential
distributions of the different cytotypes To predict the potential
distribution of S. canadensis under the current and potential future
(2050) climate, based on a climate-change scenario, we used MaxEnt
climatic niche models (Young and Evangelista 2011) and ArcGIS software.
For these models, we used 5354 occurrence data of S. canadensis, including
new data from our own research (n=150) (Li 2011, Lu et al. 2020), data
from the literature (n=321) (Table S4), records downloaded from the Global
Biodiversity Information Facility (GBIF; n=4784) and additional records
from Chinese literature (n=101). We used MaxEnt Jackknife tests (test gain
> 0.7) to select 9 key bioclimatic variables (Elith et al. 2006)
out of the 19 variables available in WorldClim (http://www.worldclim.org)
(Table S5, Fig. S8). The nine bioclimatic variables are annual mean
temperature (bio 1), isothermality (bio 3), minimum temperature of coldest
month (bio 6), mean temperature of driest quarter (bio 9), mean
temperature of warmest quarter (bio 10), mean temperature of coldest
quarter (bio 11), precipitation of driest month (bio 14), precipitation of
driest quarter (bio 17) and precipitation of coldest quarter (bio 19). The
WorldClim Current Conditions dataset (bioclimatic data averaged across the
period 1950-2000) at a spatial resolution of 10 minutes was used to model
the current climatic niche of S. canadensis. To forecast the potential
future suitable ranges for infestation, we used the climate dataset of
WorldClim for the year 2050 based on the Representative Concentration
Pathway (RCP) scenario 4.5 (http://tntcat.iiasa.ac.at:8787/RcpDb). It is a
moderate scenario where the total radiative forcing stabilizes before 2100
(Dyderski et al. 2018). For the predictions of the climatic niche
modelling, occurrence data for S. canadensis was randomly divided
according to the algorithms of the MaxEnt software into training data (75%
of occurrence points) for model prediction and test data (25% of
occurrence points) for model validation. All additional parameters were
set to their default values. A receiver operating characteristics (ROC)
curve plot was built, and the scores of the area under the curve (AUC)
indicated a good (AUC values at 0.8–0.9) to excellent (AUC values of
0.9–1.0) model fit (Fig. S9). The forecasted climatic suitability of
different areas around the globe was classified into five categories using
natural segmentation method based on clustering analysis in ArcGIS
software: unsuitable (0–0.2327), low suitable (0.2327–0.5), margin
suitable (0.5–0.6), suitable (0.6–0.7) and high risky suitable (0.7–1.0)
(Kigen et al. 2019). Supporting Information Materials and Methods
Molecular identification A pair of primers (upstream:
5'-CGTAACAAGGTTTCCGTAG-3', downstream: 5'-TTATTGATATGCTT
AAACTCAGCGGG-3') were used to amplify ITS rDNA gene and another pair
of primers (upstream: 5’-CCGCCCCTCTACTATTATCTA-3’, downstream:
5’-TCTAGACTTAGCAGCTATTG-3’) were used to amplify psbA-trnH intergenic
spacer. Polymerase chain reaction (PCR) was carried out in 50μL containing
2μL of 10μmol/L primers, 10×buffer 5μL, 25mM Mg2+ 4μL, 2.5mmol/L dNTPs
4μL, 50ng/μL DNA templates1μL and 5U Taq DNA polymerase 0.5μL. The PCR
cycle was 95°C for 4 min followed by 30 cycles of 95°C for 30s, 52°C for
60s, 72°C for 60s, and a final extension step at 72°C for 7 min. PCR
products were separated on 1% agarose gels and stained with ethidium
bromide. The PCR products were purified and sequenced. Common garden sites
and materials Two pot common garden greenhouse pot experiments were
established at Nanjing Agricultural University [Nanjing, Jiangsu, China
(32º2’N, 118º50’E), December 2011] and University of Georgia [Athens, GA,
USA (33º56’N, 83º22’W), December 2012]. Seeds from all maternal plants of
86 populations were germinated in seedling trays filled with 1:2 mixture
of soil and sterilized compost in the introduced common garden. For all of
the populations at least five individual plants were originally collected
each sampling plot but a few populations only included less than five
individuals each cytotype through detection of ploidy. The populations
with less individuals, all characterized according to cytotype by
detection of their ploidy, were considered in the experiment and their
lesser number did not significantly affect the obtained results according
to statistical tests (Supporting Data 1). Measurement of physiological and
biochemical characteristics associated with seedling thermotolerance. The
activity of Cu/Zn superoxide dismutase (Cu/Zn SOD, EC.1.15.1.1) was
measured by test Kit (Nanjing Jiancheng Bioengineering Institute, China;
A001-4). The activity of peroxidase (POD, EC 1.11.1.7) was .measured by
Guaiacol method (Li et al. 2013). Catalase activity (CAT, EC.1.11.1.6) was
.measured by test Kit (Nanjing Jiancheng Bioengineering Institute, China;
A007-1-1) (Yong et al. 2008). Glutathione reductase (GR, EC.1.6.4.2) was
measured by test Kit (Nanjing Jiancheng Bioengineering Institute, China;
A062-1-1) (Li et al. 2017). Protein content was detected by the method of
coomassie brilliant blue (Deng 2013). The H2O2 concentration was detected
by monitoring the absorbance of the titanium- peroxide complex at 415 nm,
following the method of Patterson (Brennan & Frenkel 1977).
Reproductive traits Growth of all potted plants was regularly monitored in
both the native and introduced common gardens. Flowering phenology was
assessed after onset of flowering (first flower head open), peak flowering
(>50% flower head open) and end of flowering (>50% flower
heads closed); in each plant flowering dynamics was recorded for every
shoot (capitulescence) at 3-d intervals. The duration of flowering per
plant (days between onset and end of flowering) was determined.
Infructescences of all flowering individuals were bagged before seeds
matured and dispersed. After seed matured, infructescences per plant were
harvested, dried naturally and weighed. The number of seeds of each plant
was estimated from the average 500-seed weight of five samples per
population. The number of viable seeds was estimated by the number of
seeds and the germination rate at 25°C per population. Five individuals
per population were recorded and measured (Table S3 E1, E4).
Cross-compatibility experiments A group of seedlings representative of the
six geo-cytotypes was sown every 40 days (beginning Jan. 15, 2012) to
ensure synchrony of their flowering periods. Two plants matching in
flowering period from the six geo-cytotypes were selected at the early
flowering stage for reciprocal crossings. The positive and reverse crosses
were made in all possible combinations between paired individuals
belonging to the six different geo-cytotypes (three each from native and
introduced ranges). Three populations were selected from each cytotype
except for single introduced diploid (Table S3 E7). For each cross, three
individual plants from each population were used; each one was considered
a replication. Additionally, two kinds of artificial self-pollinations
were defined as controls: those of different individuals within each
cytotype and those of different florets of same individual.The same
procedure was used to select the individuals for artificial
self-pollination.  For same individual, artificial
self-pollinations were made between different clonal shoots from a
maternal plant, different capitula on the same shoot and different tubular
florets within a single capitulum. The bisexual tubular florets in the
capitulum were carefully removed and the emasculation capitula were
isolated with paper bags. After 5-7 days, plants were artificially
pollinated when the stigma of ligulate flowers grew out of the petals and
showed a “Y” shape. The pollen of selected male parents was collected with
a brush and applied to the column head of the emasculation female parent
and the paper bags were replaced quickly after pollination. Capitula were
collected at 1h, 2h, 4h, 8h, 24h, 48h, and 72h after pollination (Fig.
S5d), and thereafter gathered every 3 days, fixed with Carlo fixation
liquid for further observation of pollen tube growth and embryo
development. The mature seeds from each cross-combination were carefully
harvested and their germination was tested at 25°C. At the full-bloom
stage of the S. candensis, six capitula from each of five populations per
geo-cytotype were selected to determine their pollen vitality with the
benzidine method (King 1960) (Table S3 E5). Briefly, new blooming
capitula, collected between 9:00 and 11:00hrs in a sunny day, were placed
into concave slides, followed by the addition of reagent I (0.5% biphenyl
10ml, 0.5% alpha naphthol 10ml, 0.25% sodium carbonate 10ml) and 0.3%
hydrogen peroxide. Capitula were mashed and the mixture was transferred
into a 1.5ml centrifuge tube and incubated for 50 min at 30°C. Stained
pollen grains were observed and photographed with a microscope (Olympus
BX53). Vigorous pollen grains stained black while the undynamic pollen
grains stained yellow. Ten visual fields of each slide were randomly
selected for assessment. To determine stigma receptivity, capitula were
also collected as described before (Table S3 E6). The florets were placed
into concave slides, followed by the addition of the staining
benzidine-hydrogen peroxide solution (1% benzidine: 3% hydrogen peroxide:
H2O = 4:11:55 volume ratio), and observed under the same microscope.
Vigorous stigma stained blue and produced a large number of bubbles. Nine
florets per geo-cytotype were observed and counted. Additional capitula
were soaked in 70% ethanol for 30 min and for additional 30 min in 90%
ethanol after fixation with Carnoy's fluid for at least 24 hour.
Then, the capitula were preserved in 70% ethanol. Before observation,
capitula were rehydrated sequentially in 50%, 30%, 10% ethanol and
distilled water for ten min each, softened in 6 mol/L NaOH for eight
hours, washed three times with distilled water and stained with 0.1%
aniline blue for 12 hours. The number of pollen grains germinating on the
stigma and pollen tubes growing into the ovary were counted under the
fluorescence microscope (Carl Zeiss, Axio Observer Z1), after making
microscopic slides of tissue samples. Thirty single flowers of each cross
combination were observed and counted. After artificial pollination,
capitula were sampled and fixed in formalin–acetic acid–alcohol (Berlyn
& Miksche 1976) (FAA) at different embryonic developmental stages.
Before observation, capitula were immersed orderly in 50% alcohol, 30%
alcohol, 10% alcohol and distilled water every ten min. Individual flowers
were carefully separated from capitula with forceps and immersed and
softened in 2.5 mol·L-1 NaOH solution for six hours, and washed three
times with distilled water. The single flowers were carefully placed on a
slide and stained by aniline blue - lactic acid - phenol dye solution (Hu
1994) for five min. Before dropping 40% glycerol on individual flowers,
redundant dye solution was absorbed by filter paper. Single flowers were
covered with slide cover slips. The number of normal embryos at the
different development stages was counted under the light microscope
(Olympus BX53) (Table S3 E3). The normal development and abortion process
of embryo is illustrated in Fig. S6: After pollination, the developing
proembryo could be observed within 24 hours, globular embryos, the
spherical embryo formed in 3~5 days after pollination (DAP), the
heart-shaped embryo formed in 6~8 DAP, the torpedo-shaped embryo formed in
20~25 DAP and gradually matured. However, in the case of the following, we
considered to be abnormal: 1, the development of embryos is seriously
lagging. 2, the periphery of the embryo is transparent and the embryo
atrophy or cluster. 3, the embryo is severely atrophied and only some
small irregular clusters can be observed inside the peel. 4, only
pericarp, no embryos and clusters can be observed inside the peel.
Prediction of potential geographical distribution of S. canadensis
Occurrence data We searched published information on chromosome numbers of
S. canadensis in relation to location in ISI-indexed journals, books and
in cytological indices [Index of Plant Chromosome Numbers (IPCN);
International Organization  of Plant Biosystematics (IOPB)
Chromosome Number Reports] (Table S4) and sampled wild populations in the
native and introduced range (Table S3). Environmental variables, isotherms
and processing of environmental data The “Current Conditions” (Current
Conditions 1950~2000) bioclimatic dataset was used to extract the current
ecological niche of S. canadensis. For simulation of the future suitable
region, we used the future climate dataset in the RCP4.5 scenarios
(http://tntcat.iiasa.ac.at:8787/RcpDb) provided by the Coupled Model
Intercomparison Project (CMIP). The RCP 4.5 is developed by the MiniCAM
modeling team at the Pacific Northwest National Laboratory's Joint
Global Change Research Institute (JGCRI). It is a stabilization scenario
where total radiative forcing is stabilized before 2100 by employment of a
range of technologies and strategies for reducing greenhouse gas emissions
and has a higher priority. We simulated the distribution of suitable
region in the future climate change scenarios based on the current
ecological niche of S. canadensis. The future climate dataset of RCP4.5
was used to drive the ecological niche modeling, before that it should be
treated with the following: (1) the value of each environmental variable
corresponding to all records in the current climate data layer was
extracted by the spatial data processing tools of ArcGIS, (2) the value
was assigned a value of background pixels at corresponding position in the
future climate data layer. Data processing Occurrence data of S.
canadensis was randomly divided according to the algorithms of the
software (MaxEnt) itself into training data (75% of occurrence point data
used for model prediction) and test data (25% of occurrence point data
used for model validation) with all additional parameters set as default.
A receiver operating characteristics curve (ROC) plot was built by
plotting the sensitivity values and the false positive fraction for all
available probability thresholds (Manel et al. 2001) (Fig. S9). The area
under the curve (AUC) was a measure of the area under the ROC, ranging
from 0.5 to 1.0. The higher the AUC score, the better the model is at
predicting presence/absence, indicating the environmental variables have
high correlation with the predicted distribution of species, and
prediction of the model is of high validity. The predicted model can be
invalid (AUC value is lower than 0.6), poor (AUC value is 0.6–0.7), fair
(AUC value is 0.7-0.8), good (AUC value is 0.8–0.9) and excellent (AUC
value is 0.9–1.0) (Swets 1988). Using a heuristic estimation during
training of the model and by means of a jackknife test, the importance of
each environmental variable in the model was evaluated (Fig. S8). The
model was visually exhibited in ArcGis (version 10.0) to produce a single
final distribution map. Different map colors corresponded to different
fitting indices in the potential distribution map. The analysis base map
was obtained from the National Fundamental Geographic Information System
(http://nfgis.nsdi.gov.cn/).
There are some missing values in the dataset: 1.) Six missing
values will be finded in antioxidative parameters of
cytotypes among native and invasive S. canadensis after heat exposure (45
ºC for 0, 2 and 4 h respectively) （File: Heat_tolerance.xlsx，Sheet:
antioxidative parameters） 2.)  In the parts of cross experiment,
29 replications were collected in some combinations，which should
be 30 replications in plan (Fig. S5h and S 6a, b, c).
Only 19 replications of the "IN6x X NA4x" ombinations
were collected in the observation of germinated pollen
grains on stigmas (Fig S 6a) and  11 replications of the
"IN4x X NA4x" ombinations were collected in
the observation of pollen tubes entering into the ovaries (Fig S
6b). 3. ) ITS sequences and psbA-trnH intergenic spacer sequences of 152
S. canadensis populations were submit the data in a
format of ".txt". You could read and
align them using MEGA 4.1 Beta 3 software.
Keywords: FOS: Biological sciences; climate niche shift; heat tolerance; pre-adaption; rapid post-introduction adaptive evolution; Solidago canadensis